An Analysis of factors affecting local income of tourism sector in Bali Province - Basuki, Agus Tri; Sugiarti, Mia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aims to analyze the effect of the number of tourists, the number of hotel rooms, the number of restaurants and GRDP on Local Original Income (PAD) in Bali Province. The model used in this study used multiple regression with panel data. This study used 9 regencies/cities in Bali Province with time seris data from 2013-2022. The selected panel data regression model is the Random Effect Model. The results showed that the number of tourists, the number of hotel rooms, and the Gross Regional Domestic Product had a positive and significant effect on the Local Original Income in Bali Province, while the number of restaurants had no influence on the local original income. Bali is a very famous tourist area, so culinary tourism is very mushrooming around tourist attractions. However, the proliferation of culinary tourism has no impact on increasing PAD. So that local governments need to re-register taxpayers for restaurant and entertainment entrepreneurs who have not paid taxes, and re-register for taxpayers who have not been recorded.